Analysis Of The Role Of Local Actors In The Governance Process Based On Sound Governance Theory. - Carlos, Samuel (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
An abstranct is a brief summary of a research article, thesis, review, conference  proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry  for any given academic  paper or patent application.  Absatrcting  and indexing services for various  academic  discipline  are aimed  at compiling  a body of literature  for that  particular  subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.